Investigating the Scope of Chaos Theory for Cyber Threat Detection - Yogi, Manas Kumar (Journal of Trends in Computer Science and Smart Technology, 2023)
The role of chaos theory in the development of cyber threat detection systems is primarily exploratory and theoretical, with limited practical adoption in recent years. Chaos theory offers interesting concepts that have the potential to enhance cyber threat detection capabilities, but its application in the cybersecurity industry faces challenges and limitations. While chaos theory's practical role in cyber threat detection systems remains limited, its principles have the potential to complement existing methodologies and inspire new approaches to address the complex and dynamic nature of cybersecurity threats. As the field progresses, staying informed about the latest research and developments can help gauge the future scope and impact of chaos theory in cyber threat detection. In this paper, the roles and the principles of chaos theory are investigated and this investigation has indicators representing ample scope of chaos theory in design and development of robust frameworks related to cyber threat detection.
Keywords: Chaos; Cyber; Threat; Security; Privacy